Transfer traumy. Monografia zbiorowa Літературний образ дитинства в часи кризи pod redakcją Katarzyny Jakubowskiej-Krawczyk - Zambrzycka, Marta (Studia Ukrainica Posnaniensia, 2022)
The text is a review of a collective monograph Літературний образ дитинства в часи кризи edited by Katarzyna Jakubowska-Krawczyk. The book is about the issues of childhood in times of crisis. Researchers from Poland and Ukraine analyze various issues, such as World War II, the Holocaust, the totalitarian regime, homelessness and the ongoing war in Donbas. The book uses the modern method of postcolonial studies and trauma research from the generational transfer perspec- tive. It deals with very important issues.